Perceptions of overdetection of breast cancer among women 70 years of age and older in the USA: a mixed-methods analysis. Issue 6 (14th June 2018) - Pappadis, Monique R; Volk, Robert J; Krishnan, Shilpa; Weller, Susan C; Jaramillo, Elizabeth; Hoover, Diana Stewart; Giordano, Sharon H; Tan, Alai; Sheffield, Kristin M; Housten, Ashley J; Goodwin, James S
Abstract : Objectives: Current research on the perceptions of overdiagnosis or overdetection of breast cancer has largely been conducted outside of the USA and with women younger than 70 years. Therefore, we explored older women's perceptions about the concept of overdetection of breast cancer and its influence on future screening intentions. Design: Mixed-methods analysis using purposive sampling based on race/ethnicity, age and educational level. Semistructured interviews, including two hypothetical scenarios illustrating benefits and harms of screening and overdetection, were analysed using inductive and deductive thematic approaches. An inferential clustering technique was used to assess overall patterns in narrative content by sociodemographic characteristics, personal screening preferences or understanding of overdetection. Setting: Houston/Galveston, Texas, USA. Participants: 59 English-speaking women aged 70 years and older with no prior history of breast cancer. Results: Very few women were familiar with the concept of overdetection and overtreatment. After the scenarios were presented, half of the women still demonstrated a lack of understanding of the concept of overdetection. Many women expressed suspicion of the concept, equating it to rationing. Women who showed understanding of overdetection were more likely to express an intent to discontinue screening, although 86% of the women stated that hearing about overdetection did not influence their screening decision. Themes identified did not differ by race/ethnicity, education, age or screening preferences. Differences were identified between women who understood overdetection and women who did not ( r =0.23, p<0.001). Conclusions: Many older women did not understand the concept of overdetection, in addition to being suspicious of or resistant to the concept. Providing older women with descriptions of overdetection may not be sufficient to influence screening intentions.